Managing potential health risks associated with drinking water supplies: some issues and approaches - Yaziz, Mohammad Ismail; Pillay, S. M. (1994)
More than 90% of Malaysia's water supplies are derived from surface water sources. Long-term monitoring programs and research data indicate that many river systems are moderately to grossly polluted by domestic and industrial wastes. Properly planned, long-term, interdisciplinary studies are needed to assess the health implications of the country's social and industrial development and the associated impacts on the quality of drinking water supplies. New areas of potential risks need to be properly evaluated and the multiple barrier concept in providing safe water supplies needs to be properly coordinated, instituted and continuously monitored.